Transformasi NU dalam Masyarakat Banjar Kini Perspektif Pergeseran Gerakan Keagamaan di Kalimantan Selatan - A.SUKRIS SARMADI (Jurnal Dialog, 2017)
This article describes the expantion of NU organization in Banjar community. Particularly, the article explain the history of the foundation of NU as supported by the clan of religious figures in the empire of Banjar that is Big Sheikh Muhammad Arsyad al Banjari. NU become more accepted in the society of Banjar. NU has adopted many elements of local cultures. Moslems in Banjar recognize Islam as a habit of NU culture. The condition of economics and social changes in modern society of Banjar have forced cultural value of NU in the city of Banjarmasin. Pasantren has become the strong bases until now for religious movement of NU.